Contextual Learning Strategy (CTL) on Mufradat Learning in IV Class of Madarasah Ibtidaiyah - Nurul Hidayah; Zulhadi Zulhadi (IJECA (International Journal of Education and Curriculum Application), 2019)
This research aims to know the process of Mufradat learning using CTL strategy in class IV MI Riadusholihin Tohir Yasin. This form of research is qualitative descriptive. Data collection methods for observation, interviews and documentation. While the analysis used is qualitative data analysis. The result of this research is the implementation of the learning of Mufradat with the CTL strategy to produce effective and efficient learning, with the steps IV Teacher class Riadussholihin Thohir Yasin set up the CTL hand out which includes: a) teachers divide the students into 2 groups according to the number of students. b) Each group is assigned to compose and attach a randomized hiwar on the cardboard that has been given by the teacher. c) Students who have more mistakes in drafting Hiwar are lost in completing the task given by the teacher and given the sanction of the winning group, namely giving each 3 Mufrada about the Isim Dhomir to be answered by the losing group. D) The winning student is entitled to a prize on condition after successfully mentioning 3 Mufradat about the Isim Dhomir he knows. e) Teachers help students conclude their group's work on the Hiwar they have learned. The use of CTL learning strategies in Mufrodat learning in class IV MI Riadusshalihin Tohir Yasin gives quite good results, according to the student's condition and in accordance with the purpose of learning Arabic IV MI Riadusshalihin Tohir Yasin but still need to improve the implementation steps of CTL Learning strategy and habituation of use of the method to get maximum results and minimize the value of the incomplete.